Comparison of SARS-CoV-2 IgG responses in hemodialysis patients and healthcare workers after COVID-19 vaccination - Öztürk, Hakkı; Özsoy, Metin; Tuna, Ayşegül; Varlibas, Artuner; Cesur, Salih; Aksoy, Altan; Çifci, Aydın; Demir, Mehmet Emin (Frontiers in Immunology, 2025)
AimThis study aimed to compare SARS-CoV-2 IgG antibody levels in hemodialysis (HD) patients and healthcare workers (HCWs) after COVID-19 vaccination and to identify factors influencing these levels.Materials and methodsA total of 193 participants were included: 104 HD patients and 89 age- and sex-matched HCWs as controls. All had completed a primary COVID-19 vaccination series (two doses of CoronaVac or BNT162b2) and a booster dose. SARS-CoV-2 anti-spike IgG was measured at least one month after the last vaccine dose using a commercial immunoassay (Abbott SARS-CoV-2 IgG II Quant, CMIA). Results in Arbitrary Units (AU/mL) were converted to WHO standard Binding Antibody Units (BAU/mL) (1 AU/mL = 0.142 BAU/mL). IgG titers ≥7.1 BAU/mL (equivalent to 50 AU/mL) were considered positive.ResultsAll participants had positive SARS-CoV-2 IgG antibodies. There were no statistically significant differences in IgG levels between HD patients and HCWs at any individual time interval (<3 months, 3–6 months, or >6 months) or in the overall mean titers (HD: 1259 ± 1112 BAU/mL; HCW: 1002 ± 765 BAU/mL; p = 0.216). No individual in either group had an IgG titer below 7.1 BAU/mL. Vaccine type, dialysis vintage, and presence of comorbidities did not significantly impact antibody levels. In the HCWs group, those vaccinated only with CoronaVac had significantly lower IgG levels than those receiving only BNT162b2 or a heterologous regimen (CoronaVac followed by BNT162b2). However, among HD patients, IgG levels did not differ by vaccine regimen.ConclusionHD patients mounted a SARS-CoV-2 IgG antibody response comparable to that of healthy HCWs, with no participant falling below the positivity threshold. Dialysis duration and comorbid conditions did not significantly affect post-vaccination IgG levels. While HCWs who received only CoronaVac showed lower antibody titers than those who received BNT162b2 or a heterologous schedule, this difference was not observed in HD patients. These results suggest that COVID-19 vaccination elicits a robust humoral immune response in the HD population, underscoring the benefit of vaccination in this high-risk group.